Performance of Footing Resting on Geogrid Reinforced Two-Layered System - Sharanamma, Mashyala; Muddaraju, H. C. (AMC Indian Journal of Civil Engineering, 2025)
The use of geosynthetic material in soil as a reinforcement improves the response of soil to loading, also it increases the normal loading and reduces disturbing shear forces. This paper presents the pressure-settlement behavior of a square load under static compression on the surface of a two-layer system (i.e., fly ash layer overlying on a sand layer) with a layer of geogrid at the interface. The results of model tests on unreinforced and reinforced two-layer systems were obtained and compared. For the reinforced condition, bi-axial geogrid was used. The study found that the bearing capacity of loose sand increased by replacing the sand layer with a fly ash layer of the required thickness. The bearing pressure was increased further and the thick-ness of fly ash was reduced by providing a layer of geogrid at the interface of the two-layer system. The results show that a lower thickness of fly ash with geogrid at the interface performs better than that with a thicker fly ash layer without reinforcement.